2021
DOI: 10.3390/ph14121271
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Tickner, Z.J.; Farzan, M. Riboswitches for Controlled Expression of Therapeutic Transgenes Delivered by Adeno-Associated Viral Vectors. Pharmaceuticals 2021, 14, 554

Abstract: In the original article, Renzl, C [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Riboswitches aid in generating viral vectors for gene therapy as well as the anti‐transgenic immune response, creating a multifunctional toolset for regulating expression in gene therapy. [ 5 ] Several research have demonstrated that the ribozyme‐based artificial riboswitch improves viral vector‐mediated gene therapy and regulation efficiency in humans and animals. [ 242 ] This riboswitch was constructed by fusing an RNA aptamer with a self‐cleaving ribozyme.…”
Section: Multidimensional Applications Of Riboswitchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Riboswitches aid in generating viral vectors for gene therapy as well as the anti‐transgenic immune response, creating a multifunctional toolset for regulating expression in gene therapy. [ 5 ] Several research have demonstrated that the ribozyme‐based artificial riboswitch improves viral vector‐mediated gene therapy and regulation efficiency in humans and animals. [ 242 ] This riboswitch was constructed by fusing an RNA aptamer with a self‐cleaving ribozyme.…”
Section: Multidimensional Applications Of Riboswitchesmentioning
confidence: 99%
“…They can respond to a wide range of endogenous and non-endogenous small molecules, making them versatile tools for various applications. While there have been several key review articles on the applications of riboswitches, with emphasis on bioimaging, gene therapy, drug targets, and food safety detection, [4][5][6][7] a full treatment of the latest advances merits a separate review. This article focuses on riboswitch applications in…”
Section: Introductionmentioning
confidence: 99%
“…Ed. 2020, 59, 22414, doi:10.1002/anie.202009240 was not cited [1]. The citation has now been inserted in Section 2.8: Regulation of CRISPR-Cas Activity by Riboswitches, paragraph 2, and should read: A particularly interesting case was recently reported by Renzl et al, who incorporated aptamers to the photoreceptor PAL into gRNAs and demonstrated 546-fold regulation of mRNA levels in response to light in HeLa cells [190].…”
Section: Missing Citationmentioning
confidence: 99%